2019
DOI: 10.1186/s12879-019-4685-9
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for the multicentre cohorts of Zika virus infection in pregnant women, infants, and acute clinical cases in Latin America and the Caribbean: the ZIKAlliance consortium

Abstract: BackgroundThe European Commission (EC) Horizon 2020 (H2020)-funded ZIKAlliance Consortium designed a multicentre study including pregnant women (PW), children (CH) and natural history (NH) cohorts. Clinical sites were selected over a wide geographic range within Latin America and the Caribbean, taking into account the dynamic course of the ZIKV epidemic.MethodsRecruitment to the PW cohort will take place in antenatal care clinics. PW will be enrolled regardless of symptoms and followed over the course of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Group two (NPZ+) included 22 samples from nonpregnant women of reproductive age from endemic areas of Mexico who had confirmed symptomatic ZIKV infection. Group three (PH) was comprised of 30 healthy ZIKV negative pregnant women, whose samples were collected as part of a linear follow-up of the ZIKAlliance protocol [ 24 ]. Group four (PWZ+) included 19 samples from pregnant women with confirmed ZIKV infection who were considered as “weakly symptomatic” because they did not meet the operational definition of Zika established in 2016, consisting of a rash with two or more of the following symptoms: fever, headache, edema, petechiae, conjunctivitis, myalgia, arthralgia, pruritus, and retro-orbital pain.…”
Section: Methodsmentioning
confidence: 99%
“…Group two (NPZ+) included 22 samples from nonpregnant women of reproductive age from endemic areas of Mexico who had confirmed symptomatic ZIKV infection. Group three (PH) was comprised of 30 healthy ZIKV negative pregnant women, whose samples were collected as part of a linear follow-up of the ZIKAlliance protocol [ 24 ]. Group four (PWZ+) included 19 samples from pregnant women with confirmed ZIKV infection who were considered as “weakly symptomatic” because they did not meet the operational definition of Zika established in 2016, consisting of a rash with two or more of the following symptoms: fever, headache, edema, petechiae, conjunctivitis, myalgia, arthralgia, pruritus, and retro-orbital pain.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between the number of study sites and unique data sets is explained by the inclusion of studies using data from a single surveillance system or multisite studies for which the metadata (e.g., source population, ZIKV assays and outcome ascertainment) did not vary across sites. For instance, the NIH/National Institute of Allergy and Infectious Diseases (NIAID)funded International Prospective Observational Cohort Study of Zika in Infants and Pregnancy study28 and the European Commission Horizon 2020-funded ZIKAlliance study29 30 each standardised outcomes definitions and laboratory procedures across sites, but due to specific differences in the source population or follow-up procedures, these studies are analysed individually by study site here. In contrast, the US Zika Pregnancy and Infant Registry31 32 is an enhanced surveillance programme including 50 states and other US territories with a shared standardised protocol contributing to a single metadata data set.…”
Section: Resultsmentioning
confidence: 99%
“…We also conducted interviews with research teams from the ZIKAlliance consortium [21] including: (a) the Industrial University of Santander, Bucamaranga, Colombia; (b) the University of Carabobo, Valencia, Venezuela; and (c) Cayetano Heredia University in Lima, Peru as case examples of locally governed biorepositories. Each of these entities had established human subject ethics approved biorepositories in response to Zika virus research needs with ability to share samples for advancing research and as reference materials.…”
Section: Methodsmentioning
confidence: 99%
“…We identified that there are many untapped and interested sites that could be contributors and users of specimens, but lack a holistic and more cohesive approach to identify and tackle the barriers to receive the benefits of sharing. An approach, centered on participation of low-and-middle income countries (LMIC), who often are at the center of new public health threats or emerging zoonotic hot zones, could prove pivotal in enabling LMIC to lead collecting and managing specimens for broader sharing [3,20,21].…”
Section: Introductionmentioning
confidence: 99%